Macrocyclic Transformations from Norrole to Isonorrole and an N‐Confused Corrole with a Fused Hexacyclic Ring System Triggered by a Pyrrole Substituent. (28th January 2016) - Li, Miao; Wei, Pingchun; Ishida, Masatoshi; Li, Xin; Savage, Mathew; Guo, Rui; Ou, Zhongping; Yang, Sihai; Furuta, Hiroyuki; Xie, Yongshu
Abstract: Three kinds of fused porphyrinoids, L2 –L4, possessing different types of corrole‐based frameworks were synthesized from a pyrrole‐substituted corrole isomer (norroleL1 ). Oxidation ofL1 afforded a unique N‐Cmeso ‐fused pyrrolyl isonorroleL2, involving the fusion of an auxiliary pyrrolic NH moiety with a meso‐sp 3 ‐hybridized carbon atom. Subsequently, L2 underwent macrocycle transformations to give singly and doubly N‐CAr ‐fused N‐confused corroles, L3 andL4, respectively.L3 andL4 contain fused [5.7.6.5]‐tetra‐ and [5.6.7.7.6.5]‐hexacyclic structures, respectively, prepared through lateral annulation. These skeletal transformation reactions from norrole to its isomer isonorrole and finally to N‐confused corrole indicate that multiply fused porphyrinoids could be readily synthesized from pyrrole‐appended confused porphyrinoids.